The development of libraries in information world/ Norzaimah Zahariman - Zahariman, Norzaimah (2012)
In this information age, the evolution of ICTs has transformed library institutions and information work towards the management trend. It influence the lifestyle nowadays where ICTs produced knowledge society which are generation who are able to stabilized and develop nation to quality of life. In order to become knowledge/Information society, the way of information handling and managing are important issues to be discussed and preserved. Due to that, the development of libraries should be maintained and upgraded based on the growth of technology.